Absorption spectra and Raman gain coefficient in near-IR region of Er3+ ions doped TeO2–Nb2O5–Bi2O3–ZnO glasses. (November 2015) - Yousef, El Sayed; Hegazy, H.H.; Almojadah, Samar; Reben, M.
Abstract: Er 3+ ions doped TeO2 based glasses were prepared by quenching melting technique. A systematic characterization of glass transition temperature and optical properties of the prepared glass was carried out. The gain cross-section for the Er 3+ laser transition 4 I 13/2 → 4 I 15/2 was calculated. The results show the TNBZ glass doped with 2000 ppm of Er2 O3 had the maximum value of gain cross-section equal to 14.4 cm −1 and large stimulated emission cross-section (1.4×10 −20  cm 2 ). The glasses developed here showed the widest bandwidths of gain cross section from 249 to 1106 cm −1 . Moreover the Raman gain coefficient of the present glass was obtained from Raman scattering experiments using 532 nm excitation. This composition has also the maximum value of Raman gain coefficient ( g =1.4×10 −10  m/W) and it has the highest value of full width half maximum (FWHM≈ 380 cm −1 ). Finally, the structure of the prepared glasses was investigated through deconvolution Raman spectra. The thermal stability and spectroscopic properties indicate that this glass doped with Er 3+ is a promising candidate for fiber lasers and Raman gain amplifiers. Highlights: The glasses TNBZ- 2000 ppm Er has large stimulated emission cross-section equal (1.4×10 −20  cm 2 ) It has Raman gain coefficient ( g =1.4×10 −10  m/W). The glasses developed here showed the widest bandwidths of gain cross section from 249 to 1106 cm −1